Foodways of the Medieval Tibetans on the Silk Road: New evidence from the Miran Site in Xinjiang. (January 2023) - Sheng, Pengfei; Zhao, Meiying; Dang, Zhihao; Allen, Edward; Tajie, Luo'sang; Ma, Tian; Jiang, Hongen
Located in the Tarim Basin in southern Xinjiang, the Miran site is well known for its so-called "winged angel" frescos and diverse cultural artifacts dating from the Han Dynasty through Tubo Kingdom (~200 BC–900 AD) periods. This essay presents the first integrated archeobotanical and isotopic investigation on the archeobotanical remains at Miran. Our findings suggest that, despite implementing mixed-crop cultivation, Tibetans at Miran became increasingly invested in drought-resistant millet-based agriculture. New seed δ 13 C data recovered from naked barley and wheat at Miran provide additional suggestions that medieval Tubo people likely employed improved irrigation techniques at this Silk Road settlement.